Likovna umetnost v Mariboru v času nemške okupacije 1941–1945 - Iskra, Anja (Studia Historica Slovenica, 2021)
The article deals with the organisation of art life in Maribor during the German occupation. Based on archival material, various aspects of the Maribor affiliate of the Graz-based association Comradeship of Styrian Artists and Friends of Art (Kameradschaft Steirischer Künstler und Kunstfreunde) are presented, as well as art exhibitions held in Maribor from 1941 to 1943. The activity of the Maribor affiliate is set in the context of the German occupation policy in Lower Styria, especially in the context of their efforts to Germanise the region and annex it to the Third Reich.
Keywords: cultural policy; exhibition policy; German occupation; Kulturna politika; likovna umetnost; Maribor (Slovenia); Nemška okupacija Slovenije (1941-1945); razstave; Sodobna likovna umetnost; visual art; Združenje štajerskih umetnikov in ljubiteljev umetnosti